A Single Cisterna Magna Injection of AAV Leads to Binaural Transduction in Mice - Blanc, Fabian; Bemelmans, Alexis-Pierre; Affortit, Corentin; Joséphine, Charlène; Puel, Jean-Luc; Mondain, Michel; Wang, Jing (Frontiers in Cell and Developmental Biology, 2022)
Viral-mediated gene augmentation, silencing, or editing offers tremendous promise for the treatment of inherited and acquired deafness. Inner-ear gene therapies often require a safe, clinically useable and effective route of administration to target both ears, while avoiding damage to the delicate structures of the inner ear. Here, we examined the possibility of using a cisterna magna injection as a new cochlear local route for initiating binaural transduction by different serotypes of the adeno-associated virus (AAV2/8, AAV2/9, AAV2/Anc80L65). The results were compared with those following canalostomy injection, one of the existing standard inner ear local delivery routes. Our results demonstrated that a single injection of AAVs enables high-efficiency binaural transduction of almost all inner hair cells with a basal-apical pattern and of large numbers of spiral ganglion neurones of the basal portion of the cochlea, without affecting auditory function and cochlear structures. Taken together, these results reveal the potential for using a cisterna magna injection as a local route for binaural gene therapy applications, but extensive testing will be required before translation beyond mouse models.